A More Dynamic Economy. (11th October 2022) - Leigh, Andrew
Abstract: Economic dynamism is fundamental to productivity and living standards. Several important metrics suggest that the Australian economy has become less dynamic over recent decades. The share of workers starting a new job has fallen. Among employing businesses, the start‐up rate has declined. On average, markets have become more concentrated. Mark‐ups have increased. Reinvigorating competition policy may be an important means of boosting dynamism and raising the rate of productivity growth.